Convergent Adaptation of Ootheca Formation as a Reproductive Strategy in Polyneoptera. (22nd February 2022) - Du, Erxia; Wang, Shuai; Luan, Yun-Xia; Zhou, Caisheng; Li, Zhaoxin; Li, Na; Zhou, Shutang; Zhang, Tingting; Ma, Wentao; Cui, Yingying; Yuan, Dongwei; Ren, Chonghua; et al.
Abstract: Insects have evolved numerous adaptations and colonized diverse terrestrial environments. Several polyneopterans, including dictyopterans (cockroaches and mantids) and locusts, have developed oothecae, but little is known about the molecular mechanism, physiological function, and evolutionary significance of ootheca formation. Here, we demonstrate that the cockroach asymmetric colleterial glands produce vitellogenins, proline-rich protein, and glycine-rich protein as major ootheca structural proteins (OSPs) that undergo sclerotization and melanization for ootheca formation through the cooperative protocatechuic acid pathway and dopachrome and dopaminechrome subpathway. Functionally, OSP sclerotization and melanization prevent eggs from losing water at warm and dry conditions, and thus effectively maintain embryo viability. Dictyopterans and locusts convergently evolved vitellogenins, apolipoprotein D, and laminins as OSPs, whereas within Dictyoptera, cockroaches and mantids independently developed glycine-rich protein and fibroins as OSPs. Highlighting the ecological-evolutionary importance, convergent ootheca formation represents a successful reproductive strategy in Polyneoptera that promoted the radiation and establishment of cockroaches, mantids, and locusts.